2020
DOI: 10.1021/acsomega.0c03449
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Synergetic Effect Analysis of the Co-Combustion of Coal Blended with Polyurethane Materials

Abstract: The synergetic effects during the co-combustion of coal blended with polyurethane are researched by thermogravimetric experiments. The mixing ratio of polyurethane to coal affects the oxygen absorption and pyrolysis. According to the synergetic effects, the co-combustion process can be divided into three stages. In the first stage, the synergetic effects are notable and the main reactions are pyrolysis and oxygen absorption. In the second stage, there are almost no synergetic effects and the main reaction is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…The weight loss was 13.63%, with the weight loss peak at 319.92 °C. The other weight loss peak was caused by the burning of depolymerization between TMA units [ 26 ]. The weight losses of Fe 3 O 4 @3DG, Fe 3 O 4 @3DG@VTMOS, and Fe 3 O 4 @3DG@VTMOS composites were 5.0, 7.0, and 29.0%, respectively, between 35–600 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The weight loss was 13.63%, with the weight loss peak at 319.92 °C. The other weight loss peak was caused by the burning of depolymerization between TMA units [ 26 ]. The weight losses of Fe 3 O 4 @3DG, Fe 3 O 4 @3DG@VTMOS, and Fe 3 O 4 @3DG@VTMOS composites were 5.0, 7.0, and 29.0%, respectively, between 35–600 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The weight loss peak was caused by the decomposition of 3DG and sialylation coated on the surface of Fe 3 O 4. The DTG curves of Fe 3 O 4 @3DG@VTMOS@TMA in Figure 2D [26]. The weight losses of Fe 3 O 4 @3DG, Fe 3 O 4 @3DG@VTMOS, and Fe 3 O 4 @3DG@VTMOS composites were 5.0, 7.0, and 29.0%, respectively, between 35-600 • C.; this makes it evident that as Fe 3 O 4 was modified to Fe 3 O 4 @3DG@VTMOS, it became more and more prone to thermal degradation.…”
Section: Characterizationsmentioning
confidence: 99%
“…Small amounts of auxiliary ingredients (catalysts, chain extenders, flame retardants and foam stabilizers) were included in the white material. According to the construction requirements, the samples were rigid polyurethane foams made of a 1:1 volume ratio mixture of black and white materials 31 . The coal and polyurethane samples were pulverized before the experiments and dried at 80 °C for 24 h in a nitrogen atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Many researches have shown that there are big differences between the pyrolysis and combustion of multiple system and single system 31 . During the spontaneous combustion process of coal-polyurethane binary system, there are synergistic effects, which greatly change the mechanism and gas release laws of spontaneous combustion 32 34 .…”
Section: Introductionmentioning
confidence: 99%
“…It showed that, in every stage, PPHC180 had synergy with coal, and this can be attributed to the non-catalytic effect associated with highly volatile matter and the porous char structure in the first two stages, and the catalytic effect of biomass ash on coal. [46][47][48] However, during the co-combustion of PLBC310 and coal (Fig. 4c), the ∆DTG exhibited only one downward peak extending from T i to T f , and the temperature corresponding to the minimum ∆DTG corresponded to the peak temperature of the actual combustion curve.…”
Section: Comparative Analysis Of Co-combustion Parameters Of Two Bioc...mentioning
confidence: 96%